Utilization of Kepok Banana Peel Waste as Composite Ingredients of Kenari (Kepok Banana Crispy) for Approaching Novel Food and Waste Management Sustainability Using Organoleptic Testing - Chandra Halim.M, S.Si; Hikmah AR; Maisarah M (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Waste is conventional problem that worsens the environmental conditions of society in Indonesia. Either inorganic or organic waste has the same role reducing the public health quality. Organic waste is easier to be processed into more useful products such as snacks. One of the organic wastes is banana peel waste. Banana peel is economic-accessible waste with large amounts of substances which is feasible managed into food products. One of the food products is crackers. Crackers are the most favorite snack in Indonesia. This research aims to utilize banana peel into crackers to increase food variation and reduce the organic waste in environment. The research methods were experimental, interviews and literature study. As the result, the highest assessment crackers achieved by 1:1 variation (tapioca flour: banana peel) with 492 points (outstanding) followed by 1:2 variation with 453 points (very good). The lowest assessment crackers achieved by 2:1 with 373 points (good). The difference of each variation depends on the taste, aroma and texture assessment. Providing banana peel to cracker mixture affects the parameter assessment as the variation 1:1 provides more crunchiness, aroma banana like and savory taste. Gradually, unbalanced variation such as 1:2 and 2:1 variation provides less crunchiness and savory taste. Banana peel waste can successfully add savory taste, crunchiness and interesting aroma of the cracker and increase society income since the cracker ingredient is more affordable. Therefore, banana peel waste can be utilized as the addition of cracker mixture in order to minimize the organic waste in Indonesia.